Antibiotic resistance profile of local thermophilic Bacillus licheniformis isolated from Maysan province soil - Banoon, Shaima; Ali, Zahra; Salih, Talal (Comunicata Scientiae, 2020)
The key concern for public health is that bacterial strains isolated from various ecosystems are immune to antibiotics used in human medicine, thus dramatically limiting therapeutic options and threatening the lives of infected people. The present study aims to reveal the antibiotics profile of fiftysix isolates of local thermophilic Bacillus licheniformis isolated from different environmental soil sites in Maysan city, Iraq. The antimicrobial agent resistance profile of B. licheniformis isolates was performed using the disc diffusion assay according to Kirby-Bauer susceptibility test protocol. The results showed that isolates were resistance against cefepime (n=56; 100%), amoxicillin (n=13; 23.3%) and ampicillin (n=52; 92.9%); and intermediate (n=56; 100%) against cephalothin and naldixic acid. The percentage resistance was low for aztreonam (n=4; 7%), chloramphenicol (n=3; 5%), clotrimazole (n=6; 10%), novobiocin (n=2; 3.5%) and ticarcillin (n=3; 5%). On the other hand, all isolates were sensitive (n=56; 100%) towards the following antibiotics: amikacin, ceftazidime, ciprofloxacin, clindamycin, imipenem, netilmycin, gentamicin, nitrofurantion, rifampin, trimethoprim and vancomycin. The results of this study suggest that the Iraqi thermophilic B. licheniformis isolates are variable in their susceptibility towards the standards antimicrobial agents. Furthermore, the presence of cefepime, amoxicillin, ampicillin, cephalothin and naldixic resistant isolates of B. licheniformis in Iraqi soils is of concern about how resistance could spread to other bacteria, and ultimately to humans.